Vapor-liquid critical temperatures and pressures of dicarboxylic acid diethyl esters. (January 2018) - Nikitin, Eugene D.; Popov, Alexander P.
Highlights: Critical properties of three dicarboxylic acid diethyl esters were measured. These compounds are thermally unstable at their critical points. Pulse-heating method with ultra-low residence times was used. Recommended values of critical properties of diethyl ethanedioate to diethyl decanedioate were determined. Abstract: The critical temperatures and pressures of diethyl esters of straight-chain saturated dicarboxylic acids C2 H5 OOC(CH2 )n−2 COOC2 H5 with n  = 5, 8, 10 have been measured. The data of this work and the results of the previous measurements have been analyzed and the recommended critical temperatures and pressures of diethyl esters from diethyl ethanedioate to diethyl decanedioate have been given. The internal consistency of the experimental data has been tested by considering the plot ( M / p c ) 1 / 2 versus n, where M is the molar mass, p c is the critical pressure. The acentric factors of dicarboxylic acid diethyl esters have been calculated.